Optimizing the Development of Micro, Small and Medium Enterprises for Filter Coffee through Improving the Quality of Human Resources in the Digital Era - Alifian Nugraha; Aldila Putri Sabrina (Institute of Computer Science (IOCS), 2022)
This research is to find out the optimization of Filter Coffee development through improving the quality of human resources in the digital era. Human resources as the main driver in a business, the role of human resources in business development needs to be improved, especially through improving the quality of human resources. Filter Coffee has limited human resources both in terms of quality and quantity therefore it is necessary to optimize business through improving the quality of human resources in order to improve business welfare. This study uses a qualitative method with a descriptive type of research that is describing facts and phenomena according to the data in the field. Collecting data through literature study, observation, interviews and documentation. By using data analysis techniques; (1) Data reduction, (2) Data presentation, (3) Conclusion/verification. There are five optimization of Filter Coffee in improving the quality of human resources, namely through increasing knowledge, skills, education, understanding of the field, ability and enthusiasm for work. The role of filter coffee human resources in the digital era has been enhanced through human resource development programs involving various business partners/coffee communities in the hope that Filter Coffee can compete in the global era.